Мотиваційна модель управління кадровим потенціалом структурних підрозділів вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2013)
Disclosed motivational model developed human resources management departments of higher education aimed at improving individual performance of its core activities.